90 world-class activities by 90 world-class trainers (J. Wiley & Sons, 2007)
The book is filled with experience and expertise. Combined, the contributors have written and edited almost 800 books and over 3,700 articles and have received hundreds of awards. Many are members of the HRD Hall of Fame and they advise some of the largest organizations in the world. Draw on their expertise and implement several of the activities. Your success is guaranteed.